2010
DOI: 10.1002/jssc.201000396
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous capillary electrophoretic analysis of inorganic anions and cations in post‐blast extracts of acid–aluminum mixtures

Abstract: Bursts resulting from the chemical reaction between hydrochloric or nitric acid with aluminum foils are very often committed by the young delinquency in western countries because of its easiness of achievement. A fast, simple, selective, and cost-effective method allowing the simultaneous detection of chloride and nitrate anions and aluminum(III) was thus required. This article focused on the development and validation of a CE method using a BGE containing 2,6-pyridinedicarboxylic acid (PDC) acting as both an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…B is Cu 2+ , Zn 2+ , Fe 3+ , Mn 2+ , and Ca 2+ that reflects the charge to size differences of the anionic metal complexes. Moreover, compared to previous works , baseline separation of Cu 2+ , Zn 2+ and Fe 3+ , Fe 2+ has also been achieved (Fig. B, C).…”
Section: Resultsmentioning
confidence: 53%
“…B is Cu 2+ , Zn 2+ , Fe 3+ , Mn 2+ , and Ca 2+ that reflects the charge to size differences of the anionic metal complexes. Moreover, compared to previous works , baseline separation of Cu 2+ , Zn 2+ and Fe 3+ , Fe 2+ has also been achieved (Fig. B, C).…”
Section: Resultsmentioning
confidence: 53%
“…, and El Rassi . Successfully electrophoretic separation of several cations were carried out in less than 12 min with 1% solution of hexadimethrine bromide and 0.01% sodium salt of polyvinylsulfonic acid coating the inner wall of the capillary . Moreover, the way to solve this problem may be also to apply a buffer system that dynamically coats the inner wall of fused capillary.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, compared to the previous studies [11][12][13], significant advancements have been made and they are discussed according to the analytes of interest. As can be seen, most of the works have focused on the analysis of cations and anions, as some of them can be considered as marker ions (after an explosion) for the potential identification of inorganic salts contained in the explosives [19][20][21][22][24][25][26][27], and only one study was devoted to the analysis of carbohydrates. [23] Apart from the analysis of high-order explosives,28 studies have also focused on environmental analysis, with only few on forensic purposes.…”
Section: Conventional Cementioning
confidence: 99%
“…Results showed that no interference anions were found, and despite not being as sensitive as IC, the high concentrations found in the real samples allowed analysis of the samples using CE, and the expected ions, chloride from the acid and aluminium (III) were detected. [20] Sarazin et al also optimized three different CE-UV methods for the analysis of anions, cations and carbohydrates, including the species of interest for the analysis of post-blast residues from explosives and IEDs, and carried out comprehensive studies on matrix interferences. [21][22][23] The method for anions sought the applicability to most of the explosive samples in order to be used by the French security forces, thus a general method was proposed.…”
Section: Conventional Cementioning
confidence: 99%